Modal Manusia, Sosial, Upah, dan Kesejahteraan: Kasus Pekerja Usaha Kecil dan Menengah - Nurlina Tarmizi Muhyiddin; Bambang Bemby Soebyakto; Fauziah Asyiek; Aning Kesuma Putri; Idham Cholid; Liliana Liliana (Society, 2021)
Capital consists of human capital, social capital, natural capital, physical capital, and financial capital, but this study will only discuss human and social capital. This study aimed to analyze the relationship between human and social capital in achieving prosperity through the level of wages and income, especially for workers in the Small and Medium Enterprises sector in Palembang City. Respondents in this research were 400 workers in the Small and Medium Enterprises sector in Palembang, in the Sub-districts of Sukarami, Ilir Barat I, Kalidoni, Seberang Ulu I and Seberang Ulu II. The method used is descriptive qualitative in path analysis, with primary data in interview questionnaires. The results showed that workers’ drinking and maximum income ranged from Rp500,000 to Rp7,500,000, with an average of Rp1,903,041. The results of the path analysis found that human capital through wages affected the income of 76.4 percent, with a beta value of 0.137 indicating that if the length of schooling were increased by 10 percent, wages would increase by 1.4 times and income by 23.6 percent. In contrast, the relationship of social capital through wages to income is very small because other factors influence, such as the work environment, place of residence, and others.